A critical review of methods for eliciting voice from children with speech, language and communication needs. Issue 4 (1st September 2020) - Bloom, Ashley; Critten, Sarah; Johnson, Helen; Wood, Clare
Abstract : In this paper we discuss the need to find suitable methods for eliciting the voices of children with communication, speech and language needs in order to gain insights into their experiences of school, especially in the context of renewed legal requirements to involve children in decisions about their education. A critical review of existing methods for eliciting and facilitating communication from children with communication needs is presented, and an analysis of those approaches is offered. From this analysis we propose a framework for the characteristics needed in any new tool developed for this purpose.